South Caucasus in Motion - World Bank Group (World Bank, Washington, DC, 2019)
The people of the South Caucasus aspire for their countries to become strong middle-class societies, and they are on track to make that aspiration a reality. Two decades of social and economic progress have changed the societies of Armenia, Azerbaijan, and Georgia. The notable improvements that people in the region have experienced are reflected in better living standards that allowed poverty to be reduced by half in the 12 years between 2005 and 2017. Yet, to consolidate middle-class societies, the governments of the South Caucasus need to do more to achieve the stability and resilience enjoyed by their more advanced peers in Europe and Central Asia. Sustainable economic growth, poverty reduction, and shared prosperity require that the full potential of all geographical and administrative areas, population groups, and economic sectors be realized. This boo analyzes spatial, social, and economic mobility in the South Caucasus. The book argues that Armenia, Azerbaijan, and Georgia have not yet integrated important geographical areas and population segments in full economic participation and social development. Economic gains have not been uniformly and equitably translated into greater welfare and opportunity among all households and individuals. The main conclusion is that sustainable growth, poverty reduction, and the consolidation of the middle class require that the institutional and physical foundations of greater and more equitable economic and social mobility be secured in the South Caucasus. Understanding and removing the constraints to the development of lagging districts; leveraging opportunities for agglomeration; linking geographical areas, peoples, and markets; fostering equality in access to better jobs; and making sure that high-quality education and basic services are available to all individuals and areas are crucial.